ANALISIS DATA KUAT TEKAN BETON TERHADAP BENTUK SAMPEL DAN MEREK SEMEN MENGGUNAKAN METODE TWO-WAYS ANNOVA: Analysis Concrete Compressive Strength Data Sample Shape and Cement Brand Using The Two-Ways Annova Method - Gunasti, Amri; Nafila, Zakya; Rifta, Azzah Iftina; F.P., Ahmad Iqbal (Universitas Muhammadiyah Jember, 2023)
Infrastructure development in Indonesia has undergone significant changes in construction materials, including concrete. This study aims to analyze the influence of sample shape and cement brand on the compressive strength of concrete. The analysis utilizes a factorial experimental design approach, with two factors: sample shape (cylinder and cube) and cement brand (Gresik, Tiga Roda, Holcim, and Merah Putih) as fixed factors. The total number of samples used is 30. Concrete compressive strength data were collected at the Muhammadiyah University Jember Laboratory, with samples immersed for 28 days. The data were analyzed using the two-way ANOVA method with SPSS software. The results of the analysis show no significant difference in the influence of sample shape on concrete compressive strength (Sig. 0.397 > 0.05). However, for the cement brand factor, there is a significant difference (Sig. 0.000 < 0.05). Statistically, there is no interaction between sample shape and cement brand on concrete compressive strength (Sig. 0.570 > 0.05). The practical application of this testing and methodology in the field of Civil Engineering, particularly in concrete technology, allows for the selection of the optimal sample shape between cubes and cylinders and the determination of high-quality cement brands for infrastructure projects.